Associated organs and system with COVID-19 death with information of organ support: a multicenter observational study - Ryuichi Nakayama; Naofumi Bunya; Takashi Tagami; Mineji Hayakawa; Kazuma Yamakawa; Akira Endo; Takayuki Ogura; Atsushi Hirayama; Hideo Yasunaga; Shuji Uemura; Eichi Narimatsu (BMC Infectious Diseases, 2023)
Abstract Background The organ dysfunction that is associated with death in COVID-19 patients has not been determined in multicenter epidemiologic studies. In this study, we evaluated the major association with death, concomitant organ dysfunction, and proportion of multiple organ failure in deaths in patients with COVID-19, along with information on organ support. Methods We performed an observational cohort study using the Japanese multicenter research of COVID-19 by assembling a real-world data (J-RECOVER) study database. This database consists of data on patients discharged between January 1 and September 31, 2020, with positive SARS-CoV-2 test results, regardless of intensive care unit admission status. These data were collected from the Diagnosis Procedure Combination and electronic medical records of 66 hospitals in Japan. The clinician identified and recorded the organ responsible for the death of COVID-19. Results During the research period, 4,700 patients with COVID-19 were discharged from 66 hospitals participating in the J-RECOVER study; of which, 272 patients (5.8%) from 47 institutions who died were included in this study. Respiratory system dysfunction (87.1%) was the leading association with death, followed by cardiovascular (4.8%), central nervous (2.9%), gastrointestinal (2.6%), and renal (1.1%) dysfunction. Most patients (96.7%) who died of COVID-19 had respiratory system damage, and about half (48.9%) had multi-organ damage. Of the patients whose main association with death was respiratory dysfunction, 120 (50.6%) received mechanical ventilation. Conclusion This study showed that although respiratory dysfunction was the most common association with death in many cases, multi-organ dysfunction was associated with death due to COVID-19.